Contemporary issues in social media marketing - Bandyopadhyay, Subir, 1958-; Rishi, Bikramjit, 1978- (Routledge, 2025)
"Contemporary Issues in Social Media Marketing provides the most cutting-edge findings in social media marketing, through original chapters from a range of the world's leading specialists in the area. This 2nd edition has been fully updated with new features such as discussion questions, global case studies and examples, and material reflecting the key trends in the field, including: 1. The growth in user-generated content, 2. The growing influence of AI in content creation, including virtual influencers. 3. The development and utilization of social media analytics. 4. The use of social media as the primary search engine. 5. The relationship between social media and the customer experience of the brand. Highly regarded for its breadth of topics, range of perspectives and research-based approach, this text is perfect recommended reading for advanced undergraduate and postgraduate students studying Digital and Social Media Marketing, Contemporary Issues in Marketing and Strategic Marketing. It will also be valuable reading for academics in the field and reflective practitioners"-- Provided by publisher.
"First edition published by Routledge 2017"--Title page verso.
Keywords: Internet marketing.; Social media -- Marketing.; Social marketing.; Customer relations.; elektronické knihy; electronic books